Interspecific interference in the closely related predatory mites Neoseiulus womersleyi and Neoseiulus longispinosus (Acari: Phytoseiidae). Issue 4 (19th May 2017) - Ullah, M. S.; Sugimoto, R.; Matsuda, T.; Wang, C.-H.; Kongchuensin, M.; Konvipasruang, P.; Gotoh, T.
ABSTRACT: Reproductive interference is known to occur in the morphologically similar species Neoseiulus womersleyi and Neoseiulus longispinosus : crosses between N. longispinosus females and N. womersleyi males produce (a few) female offspring, reciprocal crosses produce only male offspring. Details of the interspecific reproduction process remain largely unknown. In this article, we investigated intraspecific and interspecific crosses, spermathecal vesicles and spermatophores in females, and molecular identification of F1 hybrids based on the internal transcribed spacer (ITS) region of nuclear ribosomal RNA (rRNA). The copulation times of interspecific crosses were similar to those of intraspecific crosses, yet interspecific crosses between N. womersleyi females and N. longispinosus males exhibited extremely low fecundity with no female offspring. On the other hand, 1 out of 35 reciprocal crosses produced viable, but sterile female offspring (F1 ). Intraspecific crosses of N. womersleyi and N. longispinosus showed female-biased offspring sex ratios. Most N. womersleyi females (12 out of 15 females tested) that mated with N. longispinosus males had inflated vesicle(s) and were inseminated. Of the crosses between N. longispinosus females and N. womersleyi males, 14 pairs had neither inflated spermathecal vesicles nor were inseminated, and in only one pair, vesicles were inflated and insemination occurred that enabled the production of female offspring. Polymerase chain reaction products of the ITS region of rRNA gene digested with ClaI exhibited two fragments (361 and 278 bp) for the N. womersleyi and only a single fragment (642 bp) for the N. longispinosus, whereas three fragments for the F1 hybrids (642, 361, and 278 bp), confirming the identification. Our results confirmed the asymmetric reproductive interference between N. womersleyi and N. longispinosus and demonstrated that the F1 female offspring produced were (sterile) hybrids.